2022
DOI: 10.1039/d2sc04339d
|View full text |Cite
|
Sign up to set email alerts
|

Spin-state crossover in photo-catalyzed nitrile dihydroboration via Mn-thiolate cooperation

Abstract: The role of a phosphine-free SNS-pincer ligand in metal–ligand cooperative hydroboration catalysis was investigated. The bifunctional thiolate donor and spin-state change to high-spin Mn are crucial to accessing low-energy activation barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…A portion of the resulting reaction mixture was then dissolved in C 6 D 6 and transferred to an NMR tube, and the 1 H NMR spectrum was recorded. All diborylamine products were characterized by comparison with their previously reported 1 H NMR spectra. , As no side products were observed, the dihydroborated product yield was calculated based on integrals compared to the starting nitrile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of the resulting reaction mixture was then dissolved in C 6 D 6 and transferred to an NMR tube, and the 1 H NMR spectrum was recorded. All diborylamine products were characterized by comparison with their previously reported 1 H NMR spectra. , As no side products were observed, the dihydroborated product yield was calculated based on integrals compared to the starting nitrile.…”
Section: Methodsmentioning
confidence: 99%
“…57 Indeed, in our recent work on Mn-catalyzed nitrile dihydroboration, we found that thiolate donors activated HBpin by simple coordination, without B−H transfer to the metal. 50 Synthesis of phosphido-bridged complex 6 revealed the ease of pyridine ring dissociation in the NNN ligand, and the lack of reactivity of 6 with HBpin can also be attributed to weak B−P bonds (ca. 64 kcal/mol).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…To access a diamagnetic monoligated complex of manganese, MnBrCO 5 was treated with L2 and LiHMDS to give Mn­(κ 3 -SNS Me )­(CO) 3 ( 17 ) which was also not observed to undergo C aryl –S bond cleavage, even upon heating at 100 °C (Scheme B). Surprisingly, in 17 , the L2 ligand is coordinated in a facial manner, which speaks to the flexibility of this ligand despite its 5- and 6-membered ring combination …”
Section: Exploring Coordination Chemistry Of [Sns] Ligands With First...mentioning
confidence: 98%
“…While our M-[SNS] complexes demonstrated high activity as carbonyl hydroboration catalysts, we observed unremarkable reactivity with alkenes, imines, alkynes, etc . When checking for M-hydride formation in the reaction of Mn­( L2 )­(CO) 3 ( 17 ) with HBpin, we serendipitously observed the dihydroboration of acetonitrile- d 3 solvent . Optimization studies demonstrated that efficient catalysis required the use of a coordinating solvent (THF) and continuous irradiation with UV light.…”
Section: Nitrile Dihydroboration Catalysismentioning
confidence: 99%
See 1 more Smart Citation